Ngaming Customary Sanctions in the Resolution of Physical Violence Crimes in Gayo Lues: An Islamic Criminal Law Perspective - Yanti, Julida; Mustaqim, Riza Afrian; Sulfanwandi, Tgk.; Al-Faiz, Muhammad Rozaan; Aulia, Raja (Islamic Criminal Law Department, Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry, 2024)
Physical violence is an act that causes pain, injury, or serious wounds. In the Gayo Lues community, there is a customary law that regulates sanctions against perpetrators of physical violence. Adat Ngaming, one of the customs of Gayo Lues, regulates the types and levels of sanctions and the weight of the sanctions according to the purpose of forming a law. This research examines how the Ngaming customary sanctions resolve physical violence cases according to the customary law of the Marpunge Raya settlement and the review of Islamic criminal law on Ngaming customary sanctions for perpetrators of physical violence in the Marpunge Raya settlement. This research uses the empirical legal research method through library and field data collection techniques. The research results show that Ngaming customs impose sanctions on perpetrators of physical violence crimes according to the type and severity of the actions committed by the perpetrator. Violence to the head that causes a lot of bleeding (blood flowing out) is compensated with one goat, and the bleeding wound is treated (luke besalin) until healed. If the blood flows a little (does not stream), it is compensated with a chicken, and the bleeding wound is treated (luke besalin) until it is healed. The Ngaming customary sanction is by the sanctions regulated in Islamic criminal law, where wounds on the head that bleed (al-Damiyah) and wounds on the head that do not bleed (ghair al-Damiyah) are subject to legal sanctions. For physical violence on objects other than the head and face, the penalty is to pay for medical expenses until recovery, which is not regulated in Islamic criminal law because violence on objects other than the head and face has different penalties, namely, ja’ifah wounds and non-ja’ifah wounds. The penalty for a ja’ifah wound is one-third of the diyat, while the penalty for a non-ja’ifah wound is qishash.